Effects of Protected Areas on Forest Cover Change and Local Communities: Evidence from the Peruvian Amazon. (February 2016) - Miranda, Juan José; Corral, Leonardo; Blackman, Allen; Asner, Gregory; Lima, Eirivelthon
Highlights: Protected areas in the Peruvian Amazon cut deforestation by 8% in the early 2000s. Their effect on poverty in local communities is less clear. Mixed use PAs are more effective in reducing deforestation but not in cutting poverty. Summary: Protected areas are a cornerstone of forest conservation in developing countries. Yet little is known about their effects on forest cover change or the socioeconomic status of local communities. This paper assesses whether "win–win" scenarios are possible—that is, whether protected areas can both stem forest cover change and alleviate poverty. We examine protected areas in the Peruvian Amazon during the early 2000s. We find that protected areas reduce deforestation. We do not find a robust effect on poverty. Protected areas that allow sustainable extractive activities are more effective in reducing deforestation but less effective in reducing poverty.